2, 4, 6-Tribromophenol is toxic to Oreochromis niloticus (Linnaeus, 1758) after trophic and subchronic exposure. (April 2021) - Folle, Nilce Mary Turcatti; Azevedo-Linhares, Maristela; Garcia, Juan Ramon Esquivel; Esquivel, Luíse; Grotzner, Sonia Regina; Oliveira, Elton Celton de; Filipak Neto, Francisco; Oliveira Ribeiro, Ciro Alberto de
Abstract: The presence of 2, 4, 6-Tribromophenol (TBP) in the environment increased the risk of exposure to aquatic organisms affecting the animal development or metabolism. The current study investigated the low, subchronic and trophic effect of TBP in both, male and female adult of Oreochromis niloticus . The fish were exposed to 0.5 or 50 ng g −1 of TBP every ten days for 70 days. Then, hepatosomatic (HSI) and gonadosomatic (GSI) indexes, erythrocyte parameters (hemoglobin content, nuclear morphology and morphometrical abnormalities), biochemical endpoints (glutathione S -Transferase and catalase activities, non-protein thiols, lipid peroxidation and protein carbonylation levels in the liver; and acetylcholinesterase activity in the brain and muscle), histopathological analysis (liver) and vitellogenin levels (plasma) were considered. TBP affected the HSI in male and female fish, but not the GSI. Principal Component Analysis revealed that erythrocytes from males are more sensitive to TBP exposure. Likewise, TBP induced the expression of vitellogenin, CAT activity and liver lesion in male fish comparatively with control group, but GST and NPT were influenced only by sex. Finally, the results showed that the antioxidant mechanism and cholinesterase activity effects were more pronounced in male than in female. The current data shows evidences of estrogenic endocrine disruption and toxicity in O. niloticus exposed to TBP, revealing the risk of exposure to biota. Graphical abstract: Image 1 Highlights: Male and female specimens of O. niloticus fish are affected by subchronic exposure to TBP. A significant increase in HSI was observed in males only in the group treated with TBP 5 ng g −1 . TBP interferes with the activity of the enzymes CAT and AChE, lipid peroxidation and non-protein thiols. Morphological alterations were concentrated in both irreversible and reversible damages. Effects were more pronounced in male fish exposed to TBP.